(untitled) (Research, Society and Development, 2020)
Objective: To hear reports from nurses of the Family Health Center, about their knowledge on postpartum depression. Method: Field study, exploratory, descriptive, with qualitative approach, twelve nurses from eight FHC from a city in the western border of Rio Grande do Sul were interviewed. The interview technique guided by semi-structured script was used. The data were submitted to thematic analysis, a project approved by the Research Ethics Committee. Results: A PPD represents an aggravating factor to be recognized by the FHC nurses. The nurses said they were given protocols although women’s mental health is poor in training. They also reported the need for the approach and referrals of women and families to be appropriate for each context. Conclusion: A PPD is a broad topic that needs to be discussed among health professionals so that they can understand its complexity and thus conduct the necessary guidance and referrals. Although the nurses who participated in the study undertook several training courses, when it came to mental health, the approach was more generalist. We indicate the need for new research to be carried out: with managers in search of understanding why women’s mental health care has sometimes been neglected and with nurses to make them aware of their responsibility towards the prevention of women’s mental suffering. We emphasize the need to invest in the training process of nurses in order to promote more qualified care for women.